Sole Parents and Public Policy, Proceedings of a Conference held in Sydney, 30 August 1990 - Whiteford, Peter (UNSW Sydney, 1991)
We are currently experiencing an important period of change in the social circumstances of sole parents. Equally significant developments are also taking place in the policy arrangements affecting the well being of sole parents and their children. This conference, sponsored by the Social Policy Research Centre as part of its program to promote public discussion of issues in social policy, was held at an important moment it this history. The same broad patterns of change have been emerging across a number of countries whose culture and social policy frameworks are similar to ours. Some at least are deeply rooted, most significantly changes in marriage, fertility and the roles men and women play in family and paid employment. Other common trends have their basis in the economy, including changing demands for skilled and unskilled, full- and part-time workers. In a number of countries also public expenditure is increasingly tightly constrained. Common consequences have been increased numbers of sole parents and high rates of poverty among them. The social policy responses of a variety of governments have also had common elements. These have been concerned to address the scale of public expenditure of sole parents, the adequacy of public income support levels, the role of noncustodial parents, and barriers to the workforce participation of sole parents. The Conference, Sole Parents and Public Policy, examined the policy framework for sole parents taking shape in present-day Australia. The papers published here featured discussion across the broad spectrum of issues and policy instruments.
Reports and Proceedings; 89
Keywords: Sole parents; Australia; Government expenditure; Labour market; United Kingdom